The Norton anthology of literature by women: the traditon in english - Elvio Antonio Funck (Ilha do Desterro)
To be anthologized is undoubtedly a mark, if not always of excellence, at least of recognition and distinction. For reasons which cannot be investigated here, women writers have more often than not failed to receive due attention in anthologies which do not consider gender as a critical criterion. But, inally, teachers of literature by women in undergraduate and graduate English programs can now rely on an authoritative and comprehensive collection of texts. Edited and abundantly annotated by Sandra M. Gilbert (Princeton University) and Susan Gubar (Indiana University), this recent addition to the acknowledged series of Norton anthologies successfully charts and delineates a distinctively female literary tradition.